Asian elephants modulate their vocalizations when disturbed. (February 2020) - Sharma, Nachiketha; Prakash S, Vijay; Kohshima, Shiro; Sukumar, Raman
Abstract : When disturbed, animals use various modes of communication to alert conspecifics about the source of danger. Some species have evolved graded or continuous signals specific to the type of threats. African elephants, Loxodonta africana, are known to differentiate between threats from bees and humans by changing the energy concentrations of their alarm calls. However, the mechanism by which Asian elephants, Elephas maximus, use vocalizations to alert conspecifics about imminent danger remains poorly explored. To understand disturbance-induced communication in free-ranging Asian elephants, we compared two call types, 'rumbles' (low-frequency calls) and 'trumpets' (high-frequency calls), produced in disturbed (by humans or other animals) and undisturbed (social interaction) states. We then analysed acoustic characters for both call types: absolute frequency parameters including fundamental frequency (F0), mean, minimum, maximum and range; temporal parameters including call duration, time to minimum F0, time to maximum F0, peak time and minimum time; and filter-related parameters including mean, minimum and maximum of first (F1) and second (F2) formant locations. We found that under disturbed conditions, Asian elephants increased the duration of rumbles and decreased the duration of trumpets. Similarly, the mean F0 and mean positions of F1 and F2 of rumbles decreased compared with the undisturbed condition; among trumpets, no significant differences were observed in mean F0 or formant position in either F1 or F2 between the two contexts. We also found that the duration of rumbles was influenced by an interaction between group size and context: smaller groups produced longer rumbles when disturbed. These results suggest that when disturbed Asian elephants can modify vocal signals whose likely function could be to alert conspecifics about potential threats. Highlights: Asian elephants modulate both high- and low-frequency calls when disturbed. Duration of trumpets decreases and that of rumbles increases when disturbed. Fundamental frequency and formant positions of rumbles decrease during disturbance. Smaller groups produce longer rumbles when disturbed.